Applications of CRISPR/Cas as a Toolbox for Hepatitis B Virus Detection and Therapeutics - Anuj Kumar; Emmanuel Combe; Léa Mougené; Fabien Zoulim; Barbara Testoni (Viruses, 2024)
Hepatitis B virus (HBV) infection remains a significant global health challenge, leading to chronic hepatitis, liver cirrhosis, and hepatocellular carcinoma (HCC). Covalently closed circular DNA (cccDNA) and integrated HBV DNA are pivotal in maintaining viral persistence. Recent advances in CRISPR/Cas technology offer innovative strategies to inhibit HBV by directly targeting both cccDNA and integrated HBV DNA or indirectly by degrading HBV RNAs or targeting host proteins. This review provides a comprehensive overview of the latest advancements in using CRISPR/Cas to inhibit HBV, with a special highlight on newer non-double-strand (non-DSB) break approaches. Beyond the canonical use of CRISPR/Cas for target inhibition, we discuss additional applications, including HBV diagnosis and developing models to understand cccDNA biology, highlighting the diverse use of this technology in the HBV field.